Pemanfaatan E-Commerce dalam Pemasaran Kerajinan Bambu di Kelurahan Pasuluhan, Walantaka - Kota Serang - Komariah, Ade; Fikri, Riki Ukhtul; Fiana, Marista; Ningsih, Rastia; Nuryanto, Uli Wildan; Subroto, Desty Endrawati; Muti'ah, Eva; Malinda, Tia; Romlah, Siti; Maharani, Silvia (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
This community service activity aims to improve the welfare of bamboo craftsmen in Pasuluhan Village, Walantaka - Serang City, through the use of e-commerce as an effective marketing tool. In the current digital era, online product marketing has become an important strategy to expand market reach and increase the competitiveness of local products. This activity involves training for craftsmen in operating e-commerce platforms, starting from creating accounts, managing online stores, to digital promotion strategies. Apart from that, intensive assistance is also provided to help craftsmen understand market trends and optimize the use of technology in marketing bamboo craft products. The results of this activity show an increase in the knowledge and skills of craftsmen in utilizing e-commerce, as well as a significant increase in product sales via online platforms. Thus, it is hoped that this activity can contribute to increasing the income and welfare of bamboo craftsmen in Pasuluhan Village in a sustainable manner.